The Effectiveness of Interventions for Developmental Dyslexia: Rhythmic Reading Training Compared With Hemisphere-Specific Stimulation and Action Video Games - Cancer, Alice; Bonacina, Silvia; Antonietti, Alessandro; Salandi, Antonio; Molteni, Massimo; Lorusso, Maria Luisa (Frontiers in Psychology, 2020)
Developmental Dyslexia is a very common learning disorder causing an impairment in reading ability. Although the core deficit underlying dyslexia is still under debate, significant agreement is reached in the literature that dyslexia is related to a specific deficit in the phonological representation of speech sounds. Many studies also reported an association between reading skills and music. These findings suggest that interventions aimed at enhancing basic auditory skills of children with DD may impact reading abilities. However, music education alone failed to produce improvements in reading skills comparable to those resulting from traditional intervention methods for DD. Therefore, a computer-assisted intervention method, called Rhythmic Reading Training (RRT), which combines sublexical reading exercises with rhythm processing, was implemented. The purpose of the present study was to compare the effectiveness of RRT and that of an intervention resulting from the combination of two yet validated treatments for dyslexia, namely, Bakker’s Visual Hemisphere-Specific Stimulation (VHSS) and the Action Video Game Training (AVG). Both interventions, administered for 13 hours over 9 days, significantly improved reading speed and accuracy of a group of Italian students with dyslexia aged 8-14. However, each intervention programme produced improvements that were more evident in specific reading parameters: RRT was more effective for improvement of pseudoword reading speed, whereas VHSS+AVG was more effective in increasing general reading accuracy. Such different effects were found to be associated with different cognitive mechanisms, namely, phonological awareness for RRT and rapid automatized naming for VHSS+AVG, thus explaining the specific contribution of each training approach. Clinical Trial registration: ClinicalTrials.gov NCT02791841